The legal aspects of compulsory vaccinations - Ulicka, Anna (The Opole Studies in Administration and Law, 2020)
The legal aspects of preventive vaccinations are one of the elements of broadly understood sanitary law and medical law. Protective vaccinations, as one of the fundamental measures in the protection of public health, are undoubtedly an extremely efficient method for battling numerous infectious diseases. The effective implementation of the universal vaccination obligation, imposed by the legislator, ensures a high level of the population immunization and prevents the epidemic spread of infectious diseases.